Evaluasi Pelaksanaan Standar Pelayanan Minimal Rumah Sakit Bidang Farmasi Di Instalasi Farmasi Rumah Sakit Umum Daerah Pemangkat - Okke Putri Shera; Tri Murti Andayani (Fakultas Farmasi Universitas Setia Budi, 2017)
Pemangkat Public Hospital as the Regional Public Service Agency (BLUD) needs to make measurements of achievements as regards to indicators of Hosptal Minimum Service Standard that has been determined. This study aims to find out the implementation description of Hospital Minimum Service Standards in Pharmaceutical Installation of Pemangkat Public Hospital, include waiting time of drug service, the absence of error occurrence of drug delivery, customer satisfaction and the compatibility prescription according to the formularium. This study is a non experimental descriptive study with qualitative and quantitative approach. The data obtained from the observation and interview with the Head of Pharmaceutical Installation, employees, doctors and questionnaires to the outpatient. The study was conducted in December 2016. The results showed that the waiting time of drug services, the absence of error occurrence of drug delivery, and the level of customer satisfaction on pharmacy service was compatible with the standard, however the compatibility prescription according to formularium was not reached the standard.